An Innovative Multi-Disciplinary Active Learning Task Towards OBE-A Case Study - Uma Rao, K.; Prema, V. (Journal of Engineering Education Transformations, 2016)
The main objective of active learning is to shift the responsibility of learning on the learner wherein the teacher only acts as a facilitator. This is easier said than done, since the systemhas to facilitate this learning process. Active learning strategies are an integral part of Outcome Based Education, as successful completion of a task by the student, implies the effectiveness of the system and curriculum to facilitate the learning. Engineering education in India is slowly moving towards Outcome Based Education, with autonomous colleges, which have flexibility of curriculum, taking the lead. This paper presents the description, objectives, student survey and outcomes of an active learning task, called ’Self-study’ and introduced in the curriculum of undergraduate engineering students, to enhance multidisciplinary learning in students and meet various Graduate Attributes.